Feasibility of using activity trackers and apps to increase physical activity in whole families: The Step it Up Family intervention. (October 2022) - Schoeppe, Stephanie; Salmon, Jo; Williams, Susan; Power, Deborah; Waters, Kim; Alley, Stephanie; Rebar, Amanda L.; Hayman, Melanie; Duncan, Mitch J; Vandelanotte, Corneel
Objective: This study examined the feasibility of an activity tracker and app intervention to increase physical activity in whole families. Methods: This was a single-arm feasibility study with pre–post-intervention measures. Between 2017 and 2018, 40 families (58 children aged 6–10 years, 39 mothers, 33 fathers) participated in the 6-week Step it Up Family programme in Queensland, Australia. It was delivered using Garmin activity trackers and apps, weekly motivational text messages and an introductory session. Online surveys and semi-structured interviews conducted with parents assessed intervention usage, acceptability, usability, perceived usefulness, use of physical activity self-management strategies and programme influence. Analyses included descriptive statistics, Wilcoxon signed-rank test and qualitative content analysis. Results: Overall, 38 families completed the post-intervention survey (95% family retention; 90% children, 95% mothers, 88% fathers). Garmin activity tracker usage was high (i.e. nearly 24/7 during the 6 weeks intervention). Families also used the Garmin apps regularly (i.e. mostly 2–6 times per week). Further, 80% of mothers and 52% of fathers read the motivational mobile text messages. Usability and perceived usefulness of the Garmin activity trackers and apps were rated high. Both parents significantly increased their use of physical activity self-management strategies from pre to post-intervention. Parents expressed that the intervention had increased awareness of physical (in)activity in the family, encouraged to be active and promoted outdoor family activities. Conclusions: Using activity trackers and apps to increase physical activity in the whole family was well received by children and parents which suggests that this intervention approach is feasible. However, further testing is needed amongst more diverse family populations. These early findings support the implementation of a randomised controlled trial to examine intervention efficacy.